Rancang Bangun Aplikasi Monitoring dan Evaluasi Penjualan Berbasis Web Pada CV Royalty Natural Indonesia - FIOLA ILONA PUTRI; HENRY BAMBANG SETYAWAN; TONY SOEBIJONO (Jurnal Sistem Informasi Universitas Dinamika, 2021)
CV Royalty Natural Indonesia is a company engaged in cosmetic products and is a subsidiary of PT. Green Angelica, which was founded in 2011. CV Royalty Natural Indonesia provides several beauty products including royalty day cream, royalty night cream, royalty bust-up cream, royalty cleansing soap, royalty hair tonic, royalty hair shampoo, royalty hair serum, royalty hair removal, royalty mustache cream and royalty beard serum. The marketing has constantly been done through e-commerce and existing social media. However, some obstacles emerge that may cause difficulties in managing data and information, and analyzing which products that are not optimal or the most favorite. Hence, it is not possible to identify the highest and lowest demand of their products which can adversely affect the company's sales target. In view of these problems, the objective of this study is to monitor and evaluate product sales performance in order to reveal which products have the highest and lowest demand and to be able to manage product data, sales data, and customer data. Based on the results of the application testing, it can be utilized by marketing managers in managing sales and customer data. Marketing managers are also able to specify which products have the highest or lowest demand and generate the product sales reports. In addition, this platform can be used to identify further pertaining to sales reports, reports per product, product lists, and sales performance reports. The results of this study showed that Tactical Dashboard can assist the marketing managers in monitoring and evaluating product sales and the target.